Magnetic resonance imaging-derived right ventricular adaptations to endurance versus resistance training - Spence, Angela; Carter, H.; Murray, C.; Oxborough, D.; Naylor, L.; George, K.; Green, D. (Lippincott Williams & Wilkins, 2013)
Purpose: Although left ventricular (LV) adaptation to exercise training has been the focus of “athlete’s heart” research to date, information regarding right ventricular (RV) adaptation is sparse because of its complex structure and imaging technique limitations. This is the first prospective, longitudinal randomized study exploring the effect of endurance (E) versus resistance (R) exercise training on RV morphology using magnetic resonance imaging. Methods: Twenty-three young untrained men completed a randomly assigned E (n = 10) or R training protocol (n = 13) for 6 months, which was progressive, supervised, and intensive. Repeated measures included body composition, aerobic fitness, muscular strength, RV morphology (magnetic resonance imaging) and function (speckle tracking echocardiography). Results: Total lean mass increased in both groups (E = +1.3 kg, 95% confidence interval [CI] = 0.3–2.3; R = +2.1 kg, 95% CI = 1.5–3.2), whereas aerobic fitness significantly improved in E (+3.7 mL•kg−1•min−1, 95% CI = 0.9–6.5) but not in R training. Strength improved in both groups, but to a greater extent in R-trained subjects (+53.8 kg, 95% CI = 46.7–60.9 vs +35.3 kg, 95% CI = 27.3–43.4). After training, RV mass increased by 2.7 g (95% CI = −0.4 to 5.8) after E and by 1.4 g (95% CI = −1.3 to 4.1) after R training. The RV end-diastolic volume increased after E (+13.8 mL, 95% CI = 1.9–25.7), with a smaller change after R exercise (+3.9 mL, 95% CI = −6.5 to 14.3). The LV-to-RV mass ratio and myocardial function did not change in either group. Conclusion: Mild morphological RV adaptation occurred after 6 months of intense supervised E and R exercise training. The degree of change was slightly but not significantly larger after E training. RV changes mirrored those observed in the left ventricle.